1969
DOI: 10.4039/ent1011024-10
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES OF FECUNDITY AND BEHAVIOUR OF THE ORIENTAL FRUIT MOTH, GRAPHOLITHA MOLESTA (LEPIDOPTERA: TORTRICIDAE), ON THE NIAGARA PENINSULA OF ONTARIO

Abstract: Unsprayed apple trees measurably increased the numbers of the Oriental fruit moth, Grapholitha molesta (Busck), in adjacent peach trees in only 1 of 4 years, though the apples were rather heavily infested. The moth became evenly dispersed throughout a previously uninfected peach orchard within three generations. Caged orchard trees were unsatisfactory for studying behaviour because the environment within the cages differed from that in the orchard. Experimental studies indicated that fecundity of the females w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Conversely, summer generation individuals encounter conditions of abundant food and suitable microclimate, thus accumulating greater fat reserves yielding better ovipositional fitness than those experiencing long periods of adverse environmental conditions. Data furnished by Phillips and Proctor 34 infer this conclusion as well. Phillips and Proctor 34 demonstrated that overwintering OFM female fecundity was much lower than that of subsequent summer generations (7.5% versus 14% respectively).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Conversely, summer generation individuals encounter conditions of abundant food and suitable microclimate, thus accumulating greater fat reserves yielding better ovipositional fitness than those experiencing long periods of adverse environmental conditions. Data furnished by Phillips and Proctor 34 infer this conclusion as well. Phillips and Proctor 34 demonstrated that overwintering OFM female fecundity was much lower than that of subsequent summer generations (7.5% versus 14% respectively).…”
Section: Discussionmentioning
confidence: 59%
“…Data furnished by Phillips and Proctor 34 infer this conclusion as well. Phillips and Proctor 34 demonstrated that overwintering OFM female fecundity was much lower than that of subsequent summer generations (7.5% versus 14% respectively). In addition, overwintering generation egg to adult mortality apparently reduced the progeny to only 23% of those observed during either summer generations.…”
Section: Discussionmentioning
confidence: 59%
“…Examination of data based upon these factors showed no evidence of a directional effect. Phillips and Proctor (1969) reported high levels of variability in oviposition by G. molesta females in caged tree studies, with some females laying no eggs. Whereas both female and male adults may mate more than once, they rarely mate more than once within a given 24-h period (Dustan 1964).…”
Section: Discussionmentioning
confidence: 94%
“…On each shoot, three neonate larvae were placed with a camelÕs-hair brush to compensate for anticipated large levels of larval mortality (Wylie 1966, Phillips andProctor 1969). The total number of larvae placed was recorded for each tree (ranged from 24 to 210, depending upon shoot availability).…”
Section: Methodsmentioning
confidence: 99%